Anti-Double-Stranded DNA Isotypes and Anti-C1q Antibody Improve the Diagnostic Specificity of Systemic Lupus Erythematosus - Jia, Yu (Dis Markers, 2018)
OBJECTIVES: We aimed to evaluate the value of immunoglobulin (Ig) G, IgM, and IgA isotypes of anti-double-stranded DNA (anti-dsDNA) and anti-C1q antibody in diagnosing systemic lupus erythematosus (SLE) patients and elucidate their association with disease activity and lupus nephritis. METHODS: Blood samples were obtained from 96 SLE patients, 62 other autoimmune disease patients, and 60 healthy blood donors. Anti-dsDNA IgG, IgM, and IgA isotypes and anti-C1q antibody were measured by enzyme-linked immunosorbent assay. Disease activity of SLE patients was assessed according to the SLE Disease Activity Index score. RESULTS: When specificity was greater than 90%, the sensitivity of anti-dsDNA IgG, IgM, and IgA isotypes and anti-C1q antibody in diagnosing SLE was 75%, 45%, 33%, and 49%, respectively. The prevalence of anti-dsDNA IgG (p = 0.002), anti-dsDNA IgA (p = 0.028), and anti-C1q antibody (p = 0.000) in active cases was significantly higher than those in inactive ones. In addition, the presence of anti-C1q antibody was associated with renal involvement (p = 0.032). Anti-dsDNA IgM showed no significant association with disease activity, but it was inversely linked with lupus nephritis (p = 0.005). When anti-dsDNA IgG and IgA and anti-C1q were combined to evaluate SLE disease activity, the specificity reached the highest level (90%). When anti-C1q positive was accompanied by anti-dsDNA IgM negative, the specificity of diagnosing lupus nephritis was up to 96%. CONCLUSIONS: This study demonstrated the role of anti-dsDNA IgG, IgM, and IgA isotypes and anti-C1q antibody alone or combination in diagnosing SLE. Anti-dsDNA IgG and IgA and anti-C1q were shown to be associated with disease activity, while anti-dsDNA IgM and anti-C1q were associated with lupus nephritis. When the related antibodies were combined, the diagnostic specificity was significantly higher.